2023
DOI: 10.1063/5.0172549
|View full text |Cite
|
Sign up to set email alerts
|

Effect of water jet area on mitigation of vortex rope in a Francis turbine

Sandeep Kumar,
Bhupendra K. Gandhi

Abstract: The rotating vortex rope (RVR) is normally formed at part load operating conditions, which develops flow instability in the draft tube (DT) cone of a Francis turbine. The detrimental effects of RVR reduce the life and performance of the turbine. The present work mitigates RVR through axial water jet injection in the DT cone. This paper extends the author's previous work on water injection with a 50% reduction in the water jet area through two nozzles with a diameter of 12.7 mm. The effect of area reduction is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…A small turbine test rig is designed and developed by the authors and installed at the Indian Institute of Technology Roorkee (IIT Roorkee), as shown in Figure 1 [23]. The authors discussed the test setup in detail in their previous work [23][24][25][26]. A Francis turbine scale-down model 14.35:1 is used in the experimental setup [26].…”
Section: Methodsmentioning
confidence: 99%
“…A small turbine test rig is designed and developed by the authors and installed at the Indian Institute of Technology Roorkee (IIT Roorkee), as shown in Figure 1 [23]. The authors discussed the test setup in detail in their previous work [23][24][25][26]. A Francis turbine scale-down model 14.35:1 is used in the experimental setup [26].…”
Section: Methodsmentioning
confidence: 99%